The effect of linguistic intelligence and memory on air traffic control performance of field aviation polytechnic - Nisa Azhari Saragih; Gustianingsih Gustianingsih; Ridwan Hanafiah (Jurnal Pendidikan Vokasi, 2022)
Some research has been conducted to understand how general knowledge and short-term memory affect academic achievement. However, research that links these two predictors with air traffic control performance in a laboratory has not been found. Twenty-four ATC cadets participated in this research. This is associative research with multiple correlation analysis that aims to find the correlation between linguistic intelligence and short-term memory toward cadets' air traffic control performance in Aerodrome Control Tower (TWR) Laboratory. The research instruments used are oral proficiency interview, Intelligence Structure Test (IST), and air traffic control simulation. Data obtained, then, are analyzed by using the product-moment method of correlation. The results show that there is a positive correlation among the three variables with the level of closeness that falls in the high category that can be seen from the correlation coefficient value. In fact, linguistic intelligence and short-term memory both contribute to air traffic control performance during simulations. These findings offer several implications for the training program to promote success in learning air traffic control, especially in the laboratory.